Longitudinal Follow-Up of Adult Survivors of Ewing Sarcoma: A Report from the Childhood Cancer Survivor Study (CCSS) - Marina, Neyssa M. (Cancer, 2017)
BACKGROUND: Ewing sarcoma survivors (ESS) are at increased risk for treatment-related complications. The incidence of treatment-related morbidity and late mortality with aging is unknown. PATIENTS AND METHODS: This study reports survival probabilities, estimated by the Kaplan-Meier method, and cumulative incidence of cause-specific mortality and chronic conditions among ESS in the Childhood Cancer Survivor Study who were treated between 1970 and 1986. Piecewise exponential models were used to estimate relative rates (RR) and 95% confidence intervals (CI) for these outcomes. Chronic conditions were graded using CTCAE version 4.03 RESULTS: Among 404 5-year ESS (median age at last follow-up 34.8 years, range 9.1-54.8 years), 35-year survival was 70% (95% CI 66%-74%). Late recurrence (cumulative incidence 15.1% at 35 years) was the most common cause of death followed by treatment-related causes (11.2%). There were 53 patients with subsequent neoplasms (cumulative incidence 24.0% at 35 years), 38 were malignant (14.3% at 35 years). Standardized incidence ratios were 377.1 (95% CI 172.1-715.9) for osteosarcoma, 28.9 (95% CI 3.2-104.2) for acute myeloid leukemia, 14.9 (95% CI 7.9-25.5) for breast cancer, and 13.1 (95% CI 4.8-28.5) for thyroid cancer. Rate of chronic conditions were highest for musculoskeletal [RR 18.1, 95% CI 12.8-25.7] and cardiac complications [RR 1.8, 95% CI 1.4-2.3]. At 35 years from diagnosis, the cumulative incidence of any and 2 or more chronic conditions were 84.6% (95% CI 80.4-88.8%) and 73.8% (95% CI 67.8-79.9%). CONCLUSIONS: With extended follow-up, ESS' risk for late mortality and subsequent neoplasms do not plateau. Treatment-related chronic conditions develop years after therapy, supporting the need for life-long follow-up.